POST-ISLAMISME: MEMAHAMI AKSI POLITIK ISLAM KONTEMPORER - Karim, Syahrir (JPP (Jurnal Politik Profetik), 2021)
Post-Islamism is a dynamic Islamic political phenomenon that spreads with various characters. Previously ideologically different groups tried to merge into the same movement and tried to compromise or even fight. Islamic groups or mass organizations that tend to compromise with the state are their way to continue to exist in political reality. Although actually some of them still do not abandon the goals or ideology of the organization totally. This is purely to maintain public sympathy and on the other hand, to exist in the dynamics of state politics. This phenomenon is in line with several main characteristics of post-Islamism, among others, they tend to be pragmatic, tend to compromise with the state without completely abandoning their ideological characteristics, and they tend to be more realistic in seeing the situation. It can be seen that post-Islamism tends to be less in tune with issues of secularism and on the other hand they also reject the application of Sharia law which looks rigid, including ideological-religious platforms in its application in several places. In general, the characteristics of post-Islamism tend to be the same, such as compromise with political realities, pragmatic tendencies in carrying out government programs, and a tolerant attitude towards groups that are considered different with them.